Comportamento higrotérmico e energético de painéis de vedação vertical externa em madeira para a zona bioclimática 2 - Buligon, Liliane Bonadiman (2021)
Buildings without moisture control can have the durability of materials, thermal comfort and indoor air quality reduced, providing a favorable environment for the development of mould. Therefore, studies on the application of wood as a component of wall panels in civil construction can contribute to the evaluation of the hygrothermal behavior especially in humid regions, such as in Bioclimatic Zone 2. The aim of this study is to evaluate the hygrothermal and energetic behavior of different external wall panels of sawn wood (pine, eucalyptus and cumaru) and OSB, for Bioclimatic Zone 2. The methodology was divided into six steps: (1) definition of materials, (2) determination of thermal properties of wood, (3) definition of external wall panels, (4) update of the climate file TMY2 of Santa Maria, RS, (5) evaluation of thermal and energetic behavior, through computational simulation by using EnergyPlus (version 8.7) and (6) hygrothermal behavior using WUFI Pro 6.5. Thus, 9 wall panels were defined for each type of wood analyzed (pine, eucalyptus and cumaru), which were evaluated for thermal behavior, mainly from the adaptive comfort model, and for hygrothermal behavior, analyzing the integration of flows, moisture content for each layer, total moisture content, risk of vapor condensation and risk of mould growth. The results show that, for all wood species, the system composed of two wood panels and mineral wool as an intermediate layer was identified as the most advantageous, being the simplest among those with the highest annual comfort. In addition, the pine systems had the highest number of panels with good comfort indices, also presenting higher indices in relation to the eucalyptus and cumaru systems. In pine and cumaru systems there was no risk of vapor condensation. On the other hand, the panels presented hygroscopic conditions favorable to the mould growth, however the calculated growth rates were acceptable. The panels in cumaru showed the lowest values and the panels in eucalyptus showed the highest indices. Furthermore, the eucalyptus panels showed critical points for the mould growth in the outer layer. In general, the wood panels showed satisfactory behavior in terms of thermal comfort and hygrothermal behavior, highlighting the applicability of wood as a wall panel even in unfavorable weather conditions.